2019
DOI: 10.1108/ijcthr-05-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the holiday tourism constraints of mono- and bicultural people

Abstract: Purpose This study aims to investigate whether the three-dimensional leisure constraints model which is adapted to holiday tourism shows the same structure for mono- and bicultural people and perceptions of these groups differ from each other. Design/methodology/approach Separate surveys are conducted on Turkish people who are resident in Turkey, representing the mono-cultural structure, and Turkish people who live in Germany, representing the bicultural structure. The model is tested by factor analysis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…These include essential natural tourism [40] and cruise tourism [14]. Adopting factor analysis, many travel scholars have confirmed this three-dimensional leisure constraint framework to be effective and reliable [41].…”
Section: Low-carbon Travel Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…These include essential natural tourism [40] and cruise tourism [14]. Adopting factor analysis, many travel scholars have confirmed this three-dimensional leisure constraint framework to be effective and reliable [41].…”
Section: Low-carbon Travel Constraintmentioning
confidence: 99%
“…Tourism research has determined a lack of friends as the primary interpersonal constraint [40,41]. However, only a few studies have mentioned the interpersonal constraint of lack of friends in the low-carbon travel context.…”
Section: Interpersonal Constraintsmentioning
confidence: 99%
“…It is involved a high degree of uncertainty if the risks perceptions toward a destination are caused by unfavourable events (Aziz, Long, Murad, 2021). Certain previous studies showed that how perceived travel risk can influence tourists' decision-making process, such as Lai, Li and Harrill (2013) indicated that time, distance, security, visa acquisition, and money are risk components influence Chinese tourists to visit the US and Davras, Caber and Crawford (2018) stated that tourists' psychological attributes are important predictors of structural constraints in a tourism context. Nevertheless, Aziz, Long and Murad (2021) indicated that such components of risks are unable and unstable to predict tourists' performance to visit a destination due to the fact that those attributes may change over time.…”
Section: Extension Of Tpb -Perceived Without Travel Riskmentioning
confidence: 99%
“…Therefore, tourists' willingness to travel or participate in a leisure activity decreases when there is an absence of companions (Aziz, Long, Murad, 2021). Nevertheless, this type of risk may not be influential if a leisure activity could be performed without any partners (Davras, Caber, Crawford, 2018). Considering SN refers to tourists' perceived social pressure and opinions from significant others (e.g., close-friends, family members, relatives, colleagues, etc.…”
Section: Extension Of Tpb -Perceived Without Travel Riskmentioning
confidence: 99%
See 1 more Smart Citation